2018
DOI: 10.3390/su10113873
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Evolution of Industrial Symbiosis with a System Dynamics Model: A Case Study of Hai Hua Industrial Symbiosis, China

Abstract: Industrial symbiosis (IS) is a key sub-field in industrial ecology. The field itself assists in developing strategies that support local and regional sustainable development. The evolution of IS is an important topic to be explored. In this paper, we use the system dynamics (SD) method to establish a model of the evolution of industrial symbiosis in the case of Hai Hua Industrial Symbiosis (HHIS). In this model, different scenarios for energy consumption, solid waste utilization, and wastewater utilization wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 74 publications
(142 reference statements)
0
25
0
Order By: Relevance
“…Regulations and policies were most often referred to as being important for encouraging or limiting the establishment of industrial symbiosis relationships [85,111,122,169]. While the decision to establish a symbiosis relationship is made by a given entity, the role of policies is critical in encouraging this practice.…”
Section: Strategies For Overcoming the Barriers To The Realisation Ofmentioning
confidence: 99%
“…Regulations and policies were most often referred to as being important for encouraging or limiting the establishment of industrial symbiosis relationships [85,111,122,169]. While the decision to establish a symbiosis relationship is made by a given entity, the role of policies is critical in encouraging this practice.…”
Section: Strategies For Overcoming the Barriers To The Realisation Ofmentioning
confidence: 99%
“…Models developed with a system dynamics approach ( [10], [11]) tend to represent the park and plant level. These models are developed in a top-down manner, but they don't provide hierarchical model elements.…”
Section: Related Work: Simulation Reviewmentioning
confidence: 99%
“…The linking mechanism inside industrial symbiosis can be a bilateral sharing, a cascade sharing or a sharing according to the nucleus principle, which refers to a central supplier of secondary raw materials as a core of an industrial symbiosis [56]. According to [57], the emergence of industrial symbiosis can be identified by six factors: Resource (resource scarcity and availability of waste), government (regulations and standards and financial support), economy (economic benefit, financial payback and new business opportunities), company (short mental distance, trust, security and awareness), technology (technology innovation) and society (social organization or support system).…”
Section: Sharing Resources Through Industrial Symbiosismentioning
confidence: 99%